DESAIN ALAT BANTU PACKING PADA PEKERJAAN MEBEL DI PERUSAHAAN WOOD PRODUCTION - Marianti, Yuli; Arista, Anggia (Computer Science and Industrial Engineering, 2021)
ABSTRACT In the are of globalization, which requires workers to achive the productivity previously determined by the company. So that the company gets the trust of consumers. In the production process, productivity holds the three pillars that support the success of productivity,quantity (quantity), safety (safety), quality (quality). When productivity is achieved, workers often experience complaint due to uncomfortable working methods and their work is also done repaetly or repeattively. Repetitive work can cause muculuSceletas disorders, namely the occurrence of injuries to the muscles,nerves,tendons, and bones. Complaints of musculusceletal disoerders can be cause by several factors, namely the wrong way of working, work tools, that are not suitable for their use, work stations that are not suitable for their workers. The research of objective of the problem formulation is to find out how the form of packaging for furniture workers at PT. Royce Enterprise Co. Approach to the antropometric method is a field that supports ergonomics, especially in the design of equipment that has ergonomic principles. The term antropometry begins with two syllable, namely “antro” which means human, while “metri” which mean measure. So that the definition of antropometry is a field that explores the measurement of the dimensions of the human body.